Impact of different 3D regions of interest on quantifying dynamic lumbar vertebral microstructure in ovariectomized rats—a micro-CT study - Xu, Huihui; Liu, Hong; Liu, Meijie; Li, Yan; Pan, Jinghua; Wang, Shaojun; Wang, Guowei; Liu, Xin; Liu, Ying; Hou, Xiaoqin; Zhao, Hongyan (Frontiers in Medicine, 2025)
IntroductionThe selection of regions of interest (ROIs) is crucial for accurate microcomputed tomography (micro-CT) analysis. Distinct ROI selection methods exist for lumbar vertebras in osteoporotic animal model research. However, whether different ROIs directly affect the results of quantitative micro-CT-based microarchitectural data is still unknown. This study aimed to compare the diagnostic accuracy of two commonly used ROIs of lumbar vertebras in ovariectomized (OVX) rats at different time points.MethodsRats were randomly divided into the baseline group, the sham/OVX-operated groups, with 12- or 24-weeks sham (Sham 12w or Sham 24w)/12- or 24-weeks (OVX 12w or OVX 24w)-operated group (n = 6 in every group). The fifth lumbar vertebras were collected and scanned using micro-CT. Quantitative analyses of bone microarchitecture parameters were conducted separately for the central ROI (ROI 1) and overall ROI (ROI 2).ResultsThe results indicated that the Tb.N of baseline group rats for ROI 1 was significantly lower than that for ROI 2. The Tb.Th of rats of the Sham 12w and Sham 24w groups was significantly increased compared to that of the baseline group rats using the ROI 2 analysis. The bone mineral density (BMD) and bone volume fraction (BV/TV) were significantly lower by the ROI 1 than by the ROI 2 in all groups. The BMD and BV/TV also showed a significant reduction at 24 weeks postoperatively compared with those at 12 weeks postoperatively. Bland–Altman analysis showed good consistency between the two different ROI selection methods.ConclusionThis study found that capturing peripheral trabeculas (overall ROI) does not explain the increased Tb.Th in healthy mice and decreased Tb.N in OVX mice; both findings indicate that this is evident in both ROI. Moreover, this study suggested the potential value of the central ROI (effective and quicker) for evaluating osteoporosis of the lumbar vertebras in OVX rats and provides a basis for analyzing the morphological changes of lumbar trabecular.